ARTIFICIAL INTELLIGENCE IN THE IMPLEMENTATION OF PUBLIC GOVERNANCE: PUBLIC DATA SECURITY VULNERABILITIES IN INDONESIA - Dimas Agustian; S.Y. Regif; Hendrikus Hironimus Botha; Andre Pattipeilohy; Samsul Ode (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study examines the implementation of Artificial Intelligence (AI) in public governance in Indonesia, focusing on its potential for service improvement and data security challenges. Governments globally, including in Indonesia, are increasingly utilizing AI for efficiency, policy analysis, and public services. However, increased AI-driven online services heighten the risks to personal data security and privacy, alongside broader cyber threats. Significant concerns about data privacy breaches, lack of transparency, and amplification of bias in AI systems used by governments, which can lead to unfair and discriminatory outcomes. Unregulated or unsupervised AI in government-posing risks such as data privacy breaches, legal non-compliance, operational disruption, and erosion of public trust. The use of AI has led to debates on the use of AI in public governance and its security has been extensively discussed in recent literature across multiple dimensions. Using a literature review method, the analysis shows AI has significant potential to enhance public service efficiency and quality (e.g., via chatbots and data analysis), but its implementation in Indonesia is hindered by infrastructure limitations, human resource capacity, ethical aspects, and data security vulnerabilities. Indonesia faces significant public data security vulnerabilities, marked by frequent data breach incidents and AI-driven cyberattacks, exacerbated by inadequate infrastructure, regulations, and low awareness. The study concludes Indonesia lacks comprehensive AI regulations. Strengthening technical capabilities, improving education, fostering international cooperation, updating legislation, and strict law enforcement are necessary to protect data and ensure responsible AI use in public governance.